Sistem Informasi Pelabuhan Kargo Daerah Sulawesi dan Jawa Berbasis Web GIS - Aditya Lapu Kalua; Ewangelio Lengkong; Virgini Graditya Ramengkomole (Journal of Data Science and Information Systems, 2023)
The island of Java is the most populous island in Indonesia and is also the country's economic, trade and industrial center. Therefore, this island has a number of important and strategic cargo ports to support trading activities and cargo distribution. Apart from that, Sulawesi Island, as one of the largest islands in Indonesia, has several important and strategic cargo ports for trade and distribution of cargo in the region. In order to provide better and more detailed information about Cargo Ports in Sulawesi and Java, a GIS Web-Based GIS Web-Based Information System for Cargo Ports for Sulawesi and Java was created. This information system was created using the RAD (Rapid Application Development) method, this information system uses Leaflets.